Pemberlakuan Perjanjian Baku dan Perlindungan terhadap Konsumen - Hulman Panjaitan (to-ra, 2016)
Abstract Enforcement Of Formal Agreement in practically living economic day by day it has become any requirement which does not be bargained and the purity is based on to the Freedom Principle in Chapter 1338 first (1) KUHP Civil. In effort to give protection against a consumer in Enforcement of Formal Agreement, laws No. 18 in year 1999 about Consumer Protection already managed in such a way procedure Formal Agreement what be enforced in practice with the threat of cancellation if those procedures not able to be fulfilled, namely Formal Agreement in practically can not consist of â€œKlausula Eksonerasiâ€ or clause that diverts and or to free about responsibility bussinesser. In justice practice, gets amount jurisprudence that has been cancelled with any â€œClause Eksonerasiâ€ what does being free of responsibility that person in this business and divert its to the consumer. This thing purposed as form appropriate in law protection to the consumer in court rulling related to the Enforcement of Formal Agreement in community. Kata Kunci: perjanjian baku, perlindungan konsumen